Nightmare alley [videorecording (DVD)] - Power, Tyrone, 1914-1958; Blondell, Joan; Gray, Coleen, 1922-2015; Walker, Helen, 1920-1968; Gresham, William Lindsay, 1909-1962 (Criterion collection, 2021)
"Darkness lurks behind the bright lights of a traveling carnival in one of the most haunting and perverse film noirs of the 1940s. Adapted from the scandalous best seller by William Lindsay Gresham, Nightmare Alley gave Tyrone Power a chance to subvert his matinee-idol image with a ruthless performance as Stanton Carlisle, a small-time carny whose unctuous charm propels him to fame as a charlatan spiritualist, but whose unchecked ambition leads him down a path of moral degradation and self-destruction. Although its strange, sordid atmosphere shocked contemporary audiences, this long-difficult-to-see reflection of postwar angst has now taken its place as one of the defining noirs of its era--a fatalistic downward slide into existential oblivion"--Container.